(untitled) (Ágora de Heterodoxias, 2021)
If a brief and very tight overview could be made of the transcendental changes that humanity has experienced, some facts could be pointed out that are common to the conditions that have marked each stage of history: technological innovations, the appearance of power groups, shared interests, promising speeches that predict improvements and transformations, even strategies that make possible the intentions of the different social actors and the political-economic systems that have given rise to and have governed the lives of human beings.